Students’ conceptual understanding and causes of misconceptions on Newton’s Law - Rania Atara Isra; Fatni Mufit (International Journal of Evaluation and Research in Education (IJERE), 2023)
The aim of this research is to examine students’ conceptual comprehension and misconception causes on Newton’s Law material with a survey research method. The data collection instruments used five-tier multiple-choice tests and teacher interview guidelines. The sample selected was 259 students from three schools with the school categories of high, medium, and low as well as three physics teachers in these schools. The research results showed that the average misconception in the high, moderate, and low-category schools was, respectively, 19.4%, 20.61%, and 37.82% with the most misconceptions of each school category, on how to describe the force acting on objects, on how to investigate the direction of motion of objects on a particular trajectory, and on how to explain Newton’s Law I and the nature of inertia. Students in low-category schools experienced more misconceptions than medium and high-category school learners. The causes of misconceptions in the three categories of schools mostly came from the personal thoughts of the learners themselves. The implication of this research is that students in all school categories tend to experience misconceptions, mainly due to personal thoughts. Teachers are advised to identify and remediate students’ misconceptions so that they do not hinder their learning progress.